EP1172 Skinning wide local excision with delayed healing for the surgical treatment of vulval intraepithelial neoplasia. (1st November 2019) - Owegie, P; Laios, A; Hutson, R
Abstract : Introduction/Background: In the management of vulval intraepithelial neoplasia (VIN), surgical excision such as wide local excision (WLE) with primary closure or superficial skinning vulvectomy has been the mainstay of treatment. WLE or SV with delayed wound healing without primary closure can be an alternative, particularly when perianal or periclitoral areas are involved with less flexibility of surrounding tissues offering less perioperative complications and better cosmesis. We aimed to assess the safety and efficacy of surgical excision with delayed wound healing in the surgical management of VIN. Methodology: We retrospectively reviewed all the cases with a biopsy proven diagnosis of (high grade) VIN, which presented to our centre between January 2010 and December 2015. All cases were followed up until June 2017. Patient clinicopatholgical characteristics were reported when available. Treatment responses, positive margins, recurrence rates, disease free intervals (DFI) were the primary endpoints. Direct surgical morbidity according to the Clavien-Dindo classification and surgical outcomes including operative time, blood loss, length of stay, hospital readmission and long-term pain were the secondary endpoints. All patients had at least one postoperative follow-up. Results: Twenty-four women underwent the treatment. Final histology confirmed the preoperative diagnosis in all cases. The margins were positive in 15/25 cases. The procedures were uncomplicated with minimal bleeding. None of the patients were readmitted for complications of surgery. Only 6/24 relapsed with a mean time to relapse 44+-26 months. All relapsed cases were marked by re-emergence of vulval lesions. All multifocal lesions relapsed. There were no cases of occult cancer during the follow-up period. One third of women responded with a letter of satisfaction at subsequent follow-up. Conclusion: Surgical excision with delayed healing is feasible and efficient for the surgical treatment of VIN. This technique should be offered irrespective of age considering the nature of the disease, the clinician´s experience, the patient characteristics and preference. Disclosure: Nothing to disclose